APLIKASI SISTEM CUCI MOBIL UNTUK EXECUTIVE CAR & CARE - Rafika Sembiring; Kevin Gunadi (Computer Technology and Information Systems, 2021)
Every year motor vehicle users always experience an increase, this is evident from data obtained from the 2017 Central Bureau of Statistics in the number of motor vehicles as much as 138,556,669. This is used by businesses to open motorbike washing services. The information system for washing motor vehicle services in cloud wash is still done manually by using bookkeeping when a transaction occurs. Processing data that is still manual causes several problems including data search difficulties, data loss and inaccurate report generation. To overcome the problem experienced by the wash wash, the researcher made an information system for motor vehicle washing services using the waterfall method. With the existence of this information system processing data becomes much easier in terms of making reports more accurate and efficient